HUBUNGAN PENGETAHUAN IBU PRIMIGRAVIDA TENTANG TANDA BAHAYA KEHAMILAN DENGAN KUNJUNGAN ANTENATAL CARE TERINTEGRASI DI PUSKESMAS HARAPAN RAYA PEKANBARU TAHUN 2017 - Hartati, Susi (Menara Ilmu, 2018)
Mother's morbidity and mortality rate is a big problem for health especially for developingcountries. Factors that cause maternal mortality and morbidity one of them because of notdetected danger signs during pregnancy due to irregular antenatal care visit. Quantitativeresearch type with survey correlation analysis, cross sectional research design.Populationof all trimester III primigravida mothers who visited antenatal care at Harapan RayaPekanbaru Public Health Center. The sampling technique is consecutive sampling of 122samples. Using primary data. The research was conducted at Harapan Raya PekanbaruPublic Health Center from September to May 2017. The research instrument usedquestionnaire. Univariate and Bivariate data analysis. The result of univariate analysis isthe majority of respondents with enough knowledge category that is 78 people (63,9%),minority of respondents with good knowledge that is 12 people (9.8%), majority ofrespondents with incomplete antenatal care visit counted 68 people (55,7% %) and theminority with the complete category made antenatal care visit as many as 54 people(44.3%). The result of bivariat analysis obtained α (0,05)> p-value (0,03). This means thatthere is a relationship between primigravida mother's knowledge about the danger sign ofpregnancy with visit of ANC integrated at Harapan Raya Pekanbaru Public Health Center.It is advisable for research sites to continue to improve the special services of pregnantwomen and carry out well the integrated antenatal care.Keywords: Knowledge, Ante Natal Care Visit, Primigravida